Boko Haram in Nigeria: Jurisdiction of the International Criminal Court - González López, Diego (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2024)
This text aims to provide a general approach to the non-international armed conflict between Boko Haram and the State of Nigeria by analysing the actors involved, the root and immediate causes and phases of the conflict, as well as a delimitation of the jurisdiction of the International Criminal Court for war crimes perpetrated by the terrorist group Boko Haram in Nigeria (State Party to the Rome Statute). In addition, a brief general commentary is made on the effectiveness of the Court as an international tribunal with the power to investigate and try persons accused of the most serious crimes against the international community.